A Consortium of Pseudomonas aeruginosa and Trichoderma harzianum for Improving Growth and Induced Biochemical Changes in Fusarium Wilt Infected Bananas - Clement Kiing Fook Wong,; Dzarifah Zulperi,; Noor Baity Saidi,; Ganesan Vadamalai, (Tropical Life Sciences Research, 2021)
Fusarium wilt of banana cannot be effectively controlled by current control strategies. The most virulent form that caused major losses in the banana production is Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc-TR4). Biocontrol of Foc-TR4 using microbial antagonists offers a sustainable and eco-friendly alternative. A consortium of biocontrol agents (BCAs), Pseudomonas aeruginosa DRB1 and Trichoderma harzianum CBF2 was formulated into pesta granules, talc powder, alginate beads and liquid bioformulations. Previous study indicated bioformulations containing both BCAs successfully reduced the disease severity of Foc-TR4. To date, the biocontrol mechanism and plant growth promoting traits of a consortium of BCAs on infected bananas have not been explored. Therefore, the study was undertaken to investigate the effect of a consortium of DRB1 and CBF2 in the growth and biochemical changes of Foc-TR4 infected bananas. Results indicated pesta granules formulation produced bananas with higher biomass (fresh weight – 388.67 g), taller plants (80.95 cm) and larger leaves (length – 39.40 cm, width – 17.70 cm) than other bioformulations. Applying bioformulations generally produced plants with higher chlorophyll (392.59 – 699.88 ?g/g FW) and carotenoid contents (81.30 – 120.01 ?g/g FW) compared to pathogen treatment (chlorophyll – 325.96 ?g/g FW, carotenoid – 71.98 ?g/g FW) which indicated improved vegetative growth. Bioformulation-treated plants showed higher phenolic (49.58 – 93.85 ?g/g FW) and proline contents (54.63 ?g/g FW – 89.61 ?g/g FW) than Foc-TR4 treatment (phenolic – 46.45 ?g/g FW, proline – 28.65 ?g/g FW). The malondialdehylde (MDA) content was lower in bioformulation treatments (0.49 – 1.19 Nm/g FW) than Foc-TR4 treatment (3.66 Nm/g FW). The biochemical changes revealed that applying bioformulations has induced host defense response by increasing phenolic and proline contents which reduced root damage caused by Foc-TR4 resulting in lower MDA content. In conclusion, applying bioformulations containing microbial consortium is a promising method to improve growth and induce significant biochemical changes in bananas leading to the suppression of Foc-TR4.